Penanaman Karakter Cinta Lingkungan Sekolah Melalui Program Daily Activities Bank Sampah Daur Ulang (Bank SADAR) sebagai Wujud Perilaku Warga Negara yang Baik di Fathia Islamic School Kota Sukabumi - Septiana, Tina; Rosmiati, Neni (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
The inculcation of the character of loving the school environment through the daily activities program or daily activity program at school is basically to apply character education to students from an early age, by implementing programs of good character values at school, it is hoped that the main characters are as stated in the vision and mission at Fathia Islamic School can be internalized to students not only in the school environment, but also in the family environment or at home and also in the community. In addition, the main goal is to shape the character of children who have good morals, not only to shape children's intelligence cognitively, but from their emotional and spiritual intelligence. The daily activities program is a series of daily activities which are a development of the Fathia Islamic Elementary School curriculum, namely an integrated and holistic curriculum (ie bringing together the curriculum concepts from the National Education Department, the Islamic dienul curriculum and the natural school curriculum). In these daily activities, there is a superior program, namely the waste recycling management program or Bank SADAR (Recycled Waste), which in this program is an activity to cultivate good character by getting used to managing waste according to its type through Bank SADAR. This flagship program is a form of good citizen behavior. A good citizen's behavior can be applied from an early age starting from a pattern of habituation or a pattern of habits that is carried out repeatedly and routinely, one of which is through a daily activity program or daily activity program at school.